Seasonal Activity of The Cambium in the Young Branch of Swietenia Macrophylla King - E.B. Hidajat; T.S. Suradinata; B.I. Utomo (Institute for Research and Community Services (LPPM) ITB, 1986)
Sari. Keragaman musim dalam aktivitas kambium pembuluh pada Swietenia macrophylla King telah diteliti mulai bulan Agustus 1983 sampai dengan Juli 1984. Di bulan Agustus aktivitas tersebut lambat dan di bulan September tampak sifat-sifat dorman. Setelah bulan-bulan kering itu aktivitas kambium kembali tampak di bulan Oktober saat curah hujan tinggi. Aktivitas terus berlangsung di bulan-bulan berikutnya dan mereda di bulan Maret. Aktivitas kambium paling tinggi berlangsung di bulan April sewaktu terjadi puncak kedua dalam curah hujan di musim hujan. Aktivitas yang tinggi ilu terjadi bersamaan dengan munculnya daun baru yang didahului oleh suatu periode gugur daun yang singkat. Aktivitas kambium mereda di bulan-bulan berikutnya. Abstract. Seasonal variation in the activity of the vascular cambium of Swietenian macrophylla King has been investigated from August 1983 to July 1984. Cambial activity is slow in August, and in September dormant features are seen. After the preceding dry months the cambium shows activity again in October when heavy rainfall occurs. The activity continues during the following months and slows down in March. The cambium is most active in April when a second peak of rainfall occurs in the rainy season. This grand activity of the cambium coincides with the emergence of a new crop of leaves which is preceded by a brief period of defoliation. Cambial activity slows down again in the following months.